North Pole legacy black, white & Eskimo - Counter, Samuel Allen (Univ. of Massachusetts Press, 1991)
Account of the lives of Anaukaq Henson and Kali Peary. The American-Eskimo sons of Matthew Henson and Robert Peary respectively, and their families in the village of Moriussaq, northern Greenland.